THE INFLUENCE OF THE IMPLEMENTATION OF PUBLIC SECTOR ACCOUNTING, ACCOUNTABILITY AND TRANSPARENCY OF FINANCIAL REPORTS ON THE PERFORMANCE OF ACEH GOVERNMENT WORK UNITS - Putri Dida Nurida (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
Nowadays in Indonesia, the reform of state financial management has entered an era of transparency and accountability. This is marked by the enactment of Law Number 17 of 2003 concerning State Finance which authorizes central and regional government agencies to make financial reports in every accountability of the implementation of the APBN/D to the DPR/D. The financial reports in question are the Budget Realization Report, Balance Sheet, Cash Flow Report and Notes to the Financial Statements. Research Results Based on the results of simultaneous tests, it can be seen that all indicators studied have an effect on improving the performance of the Aceh Government Work Unit, where the application of public sector accounting (X), accountability (X), and transparency (X,) have an effect on the performance of the Aceh Government Work Unit. shows that the application of public sector accounting partially affects the performance of the Aceh Government Work Unit. These results indicate that the application of public sector accounting will have a real impact on improving the performance of the Aceh Government Work Unit. The variables that affect performance in this study are limited to research variables, namely the application of public sector accounting, accountability and transparency. Public sector accounting research is advised to add variables that affect the performance of the Aceh Government Work Unit, for example the use of information technology and internal supervision. Measurement of SKPA performance in this study is limited to self-evaluation methods so that it is possible that respondents who have just held positions in the Aceh Government Work Unit have not been able to measure their own performance. Therefore, it is hoped that further researchers will combine the methods between subordinate evaluation of superiors and superior evaluation of subordinates, so that the research conducted can be generalized in an effort to provide empirical support for the theory being tested.